ISLAMIC VALUES INTEGRATION IN ENGLISH LESSON AT MADRASAH TSANAWIYAH: TEACHERS’ BELIEFS AND PRACTICES - Rohmah, Galuh Nur; Hanifiyah, Lina; Ningsih, Anita Andriya (Pusat Pengembangan Bahasa IAIN Tulungagung, 2019)
Integrating Islamic values in non-religion subjects at masdrasah has been crucial to do. This study outlines the teachers’ beliefs and practices on integrating Islamic values in English lesson at Madrasah Tsanawiyah (MTs) Jawa Timur. By using qualitative approach, this study involved 6 English as a Foreign Language (EFL) teachers from Surabaya, Malang, and Pasuruan representing the demography of the city as metropolitan city, education city, and santri city. Data were taken from classroom observation and interview which then those were analysed by firsly categorizing into some dimensions. The teachers’ beliefs were categorized into their knowledge on integration, the important of integration, and integration in English lesson as well as the supporting policy from the school. The teachers believed that the integration of Islamic values is significant in English lesson as the manifestation of K-13 focusing on KI 1 and KI 2, and school policy. The beliefs influence the teachers’ practices in which they have been trying to insert Islamic values in their teaching activities. The level of integration was still at integrating religious routines such as ‘doa bersama’, ‘reciting some Surah’, ‘warning praying time’. The integration in the content of English lesson was still not strongly practiced even some teachers have done it by giving added values when explaining a particular material. The situation was mostly influenced by inability to operationalize the values into the teaching materials and the lack of model for integration. Further study on how to operationalize the integration, and on developing the model of integration will be worth investigating.